Dominant mental states in juniors' coping behavior - Kurova, A.; Popovych, I.; Shevchenko, N.; Lialiuk, G.; Chernyavska, T.; Kolly-Shamne, A.; Yaremchuk, V.; Shcherbak, T. (Journal of Physical Education and Sport, 2025)
This study aims to identify the psychological correlations of defensive behavior and develop a factor structure of dominant mental states related to coping behavior in junior athletes.